(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The systematic composition of the algoflora of reservoirs in Uzbekistan has been studied by many researchers, while from the presented data it is clear that the data are given for 20 reservoirs, we have analyzed in detail 13 reservoirs for the content of Chlorophyta